Isokinetic Evaluation of Knee Strength and Endurance in Hemodialysis Patients Treated with the Transpatellar Tunnel Technique for Bilateral Spontaneous Quadriceps Tendon Ruptures - Birişik, Fevzi; Ekinci, Mehmet; Bayram, Serkan; Şahinkaya, Türker; Ergin, Ömer Naci; Erşen, Ali; Aşık, Mehmet (The Journal of Knee Surgery, 2020)
There are numerous surgical techniques described for treating acute quadriceps tendon rupture. We aim to evaluate the strength of the quadriceps tendon using isokinetic tests in hemodialysis patients treated with the transpatellar tunnel technique for bilateral spontaneous quadriceps tendon ruptures. Additionally, functional and clinical results were investigated and compared with hemodialysis patients without a history of quadriceps tendon rupture. We retrospectively reviewed hemodialysis patients diagnosed with quadriceps tendon rupture who were operated between 2005 and 2015 at our institution. Eight patients with simultaneous bilateral quadriceps tendon rupture treated with the transpatellar tunnel technique (group 1; the operated group) and 10 patients with chronic renal failure without a history of quadriceps tendon rupture who underwent hemodialysis (group 2; the control group) were included in this study. The active range of motion (ROM), Lysholm and Tegner scores, knee flexor and extensor muscle strengths, and endurances were measured using an isokinetic dynamometer for each group and compared between the groups. The mean age was 44.6 and 40.2 years in groups 1 and 2, respectively. The mean follow-up was 58.6 (range, 24–140) months in group 1. The active ROM was 113.7 ± 9.7 degrees in group 1 and 130 ± 4.8 degrees in group 2 (p < 0.001). The mean Tegner score was not significantly different between the groups (1.87 ± 1.1 in group 1 vs. 2.6 ± 0.9 in group 2; p = 0.212). However, the Lysholm score was significantly higher in group 2 (93.2 ± 7.3 vs. 76.7 ± 13.8; p = 0.009). The mean extensor strength and endurance were significantly higher in group 2 than in group 1. The mean flexor strength and endurance were higher in group 1 than in group 2, but no significant difference was found. Although using the transpatellar tunnel technique for bilateral spontaneous quadriceps tendon ruptures in hemodialysis patients can provide acceptable functional results, the ROM and strength particularly in extensor muscle might be significantly lower than control group. Level of evidence is Level III therapeutic case–control study.
Keywords: quadriceps tendon strength; isokinetic test; transpatellar tunnel; chronic renal failure